Ikonitas Perempuan dalam Tayangan Horor Indonesia: Telaah Semiotika pada Poster Filem 2022-2023 - Fadia Finta; Moh Atikurrahman (Indonesian language and literature education program Majapahit Islamic University, 2023)
This article aimed to investigate the sign system in Indonesian horror film posters throughout the years 2022-2023. Over the past two years, an intriguing trend emerged in relation to horror films in Indonesia, wherein iconicity involving women became the representamen of the sign system within a film poster. The research methodology used was qualitative description, with Indonesian horror films from the years 2022-2023 serving as the data source. To comprehend the meanings encapsulated within the latest Indonesian horror film posters, Charles Sanders Peirce's paradigm on signs was adopted as a reference to understand the research material – the Indonesian horror film posters from 2022-2023. The research results showed that the representation of meaning in the Indonesian horror film posters from 2022-2023, which were employed as icons within their posters, centered around women. In terms of color selection for the letters in the posters, the use of red was notable, symbolizing the color of blood. Keywords: poster, women, Indonesian horror films, Peirce